IMPLEMENTASI KEBIJAKAN PEMBIAYAAN PENDIDIKAN : (Studi di SMPN 1 Curup Timur, Rejang Lebong, Bengkulu) - Saidil Mustar (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
This study aimed to find the portrayal of financing policy implementation through the management of BOS funds at SMPN 1 Curup Timur. Viewed from the problem under study, this study was descriptive in nature, and it deployed a qualitative approach. In order to obtain accurate data related to this problem, this study used two methods, observations and interviews with the principal. Once collected, the data were further analyzed by means of the following stages: Data reduction, data presentation, and conclusion drawing. The findings of this study concluded that the implementation of Education Financing Policy at SMP 1 Curup Timur was manifested in the management of BOS funds. The procurement of BOS (School Operational Assistance) funds at this school was supported by the government, and the budgets were dependent upon the number of students with the amount of one million for one student. There were almost 700 students at this school. BOS funds were distributed every 3 months, and then there were 20% of the budgets for books and infrastructure. BOS-driven education funding, especially at SMP, was already implemented in accordance with the technical guidelines and was supervised by the local government.